2001
DOI: 10.1017/s0033822200041163
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution AMS 14C Dating of Post-Bomb Peat Archives of Atmospheric Pollutants

Abstract: Peat deposits in Greenland and Denmark were investigated to show that high-resolution dating of these archives of atmospheric deposition can be provided for the last 50 years by radiocarbon dating using the atmospheric bomb pulse. 14C was determined in macrofossils from sequential one cm slices using accelerator mass spectrometry (AMS). Values were calibrated with a general-purpose curve derived from annually averaged atmospheric 14CO2 values in the northernmost northern hemisphere (NNH, 30°–90°N). We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 30 publications
2
81
0
Order By: Relevance
“…Moreover, using such isotopic fingerprints, Weiss et al (1999) demonstrated Pb immobility by comparing Pb isotopic composition in dated herbarium Sphagnum samples from Swiss and Southern Germany and in 210 Pb-dated peat samples from the same age and same location. The similarity of age dating made using the 210 Pb CRS model and 14 C Bomb Pulse Curve also supports the immobility of Pb (Goodsite et al, 2001). Over the last few years however, as some authors have continued to investigate the behaviour of lead in peat, the debate over Pb mobility reopened.…”
Section: Mobility Of Heavy Metals In Peat -A Short Reviewmentioning
confidence: 54%
“…Moreover, using such isotopic fingerprints, Weiss et al (1999) demonstrated Pb immobility by comparing Pb isotopic composition in dated herbarium Sphagnum samples from Swiss and Southern Germany and in 210 Pb-dated peat samples from the same age and same location. The similarity of age dating made using the 210 Pb CRS model and 14 C Bomb Pulse Curve also supports the immobility of Pb (Goodsite et al, 2001). Over the last few years however, as some authors have continued to investigate the behaviour of lead in peat, the debate over Pb mobility reopened.…”
Section: Mobility Of Heavy Metals In Peat -A Short Reviewmentioning
confidence: 54%
“…The age estimates produced by one (or both) of these methods are prone to significant inaccuracy. Goodsite et al (2001) also found a discrepancy between 210 Pb and 14 C age estimates of peat profiles from Greenland and Denmark, where the 14 C dates were much younger than 210 Pb age estimates in the pre-1963 section of the core. In this study, the FI and SP cores also have a few 14 C dates before 1963 that are much younger than the 210 Pb age estimates.…”
Section: Discussionmentioning
confidence: 83%
“…Nevertheless, relatively few studies have used the 14 C bomb peak technique to date peats (e.g. Goodsite et al 2001;Donders et al 2004;Garnett and Stevenson 2004;Goslar et al 2005;Sjögren et al 2006;van der Linden and van Geel 2006;Hua 2009;Piotrowska et al 2010). Goslar et al (2005) observed that any depth increment will likely correspond to more than a single year of peat growth, with an incorporation of 14 C activities in the Sphagnum within that increment.…”
Section: Dating Techniques Bomb 14 C Datingmentioning
confidence: 99%
“…In order to check this, we compared our data with the "atmospheric" calibration curve averaged over the whole year (solid line in Figure 1) and that one averaged over the tree growing season (dashed line in Figure 1) as reported by Goodsite et al (2001). Table 1); b) tree-ring data from Acacia, Hungary (Hertelendi et al 1982); c) tree-ring and seeds (Douglas fir and cotton) data from Arizona (USA), 32°N (Goodsite et al 2001); d) annual averaged 14 CO 2 curve for the 30-90° latitude band (Goodsite et al 2001); e) atmospheric 14 CO 2 from Austria and Germany (48°N) (Levin et al 1997;Goodsite et al 2001) averaged only for the oak growing season (April to August). From Figure 1, it is clear that our data follow the annual averaged "atmospheric" curve very well, and no higher values are observed in the 14 C concentration in the tree rings.…”
Section: Resultsmentioning
confidence: 99%